Pengaruh Kegiatan Retorika Terhadap Hasil Belajar Mata Pelajaran Fikih Siswa Kelas Vii Madrasah Tsanawiyah Muhammadiyah 25 Brondong Lamongan Tahun Pelajaran 2021/2022 - Husniyah, Himmatul (STIT Muhammadiyah Paciran Lamongan, 2023)
The purpose of this study was to determine the effect of Rhetoric activities and to determine student learning outcomes in Fiqh subjects, and to determine whether there was a significant effect of Rhetoric activities on students' Fiqh learning outcomes. This study uses a quantitative approach with a total of 30 respondents, using sample data, collecting data using pre-test and post-test questions. In calculating the hypothesis, the researcher uses the product moment correlation test and shows that there is a significant effect of Rhetoric activities on student learning outcomes in Fiqh subjects, obtained the value of rxy = 0.487, and for a significant test the value of tcount = 2.951, at a significant level of 5% is 2,048. So from the discussion above, it shows that there is a positive and significant effect of Rhetoric activities on student learning outcomes in the seventh grade Fiqh subject at MTs Muhammadiyah 25 Brondong, while the influence of the Rhetoric activity factor is 23.7% obtained from the calculation of the determination test.